Frequency selective surface structure, double-layer wave-absorbing patch and preparation method

By using liquid silicone rubber of the same matrix as the silicone rubber wave absorbing patch as the substrate for printing paste, the problem of difficult to adhere to the metal FSS layer on the surface of the silicone rubber is solved, and the good bond between the FSS layer and the wave absorbing patch is achieved, which improves the simplicity and cost-effectiveness of the preparation.

CN119726140APending Publication Date: 2025-03-28陕西华秦科技实业股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821746.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, it is difficult to adhere to the metal frequency selection surface structure (FSS) layer on the silicone rubber surface, resulting in the inability to prepare a method for setting the FSS layer on the surface of the wave absorbing patch with silicone rubber as the substrate.

Method used

Liquid silicone rubber of the same matrix as the silicone rubber wave absorbing patch is used as the substrate for printing paste, so that the FSS layer and the wave absorbing patch have a good bonding effect, and the effective adhesion of the FSS layer is achieved through specific printing paste composition and preparation methods.

Benefits of technology

The good bond between the FSS layer and the silicone rubber wave absorbing patch is achieved, which solves the problem that it is difficult to adhere to the metal FSS layer on the silicone rubber surface, and improves the simplicity and cost-effectiveness of the preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119726140A_ABST
    Figure CN119726140A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of frequency selective surfaces in wave-absorbing patches, in particular to a frequency selective surface structure, a double-layer wave-absorbing patch and a preparation method.The frequency selective surface structure comprises N * M pattern units, a round hole is etched in the center of each pattern unit, and the number of the pattern units is N * M; a circular hole is formed in the periphery of the pattern unit, four L-shaped strip apertures are etched in the periphery of the circular hole at intervals, the four L-shaped strip apertures are uniformly distributed to form a square structure, each pattern unit is square, square holes are etched in four corners of each pattern unit, and any two square holes are symmetrical by taking the square structure as a center. The double-layer wave-absorbing patch containing the frequency selective surface structure comprises an FSS layer, a wave-absorbing layer and a reflecting layer which are sequentially arranged on a back plate layer from top to bottom, and the structure of the FSS layer is the frequency selective surface structure described in the claim 1. The double-layer wave-absorbing patch provided by the invention has effective absorption bandwidth and relatively high polarization stability in the whole X wave band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of frequency selective surfaces in wave absorbing patches, and in particular to a frequency selective surface structure, a double-layer wave absorbing patch and a preparation method thereof. Background Art

[0002] Frequency Selective Surface (FSS) is a surface with a special periodic structure, which is used to selectively transmit, reflect or absorb electromagnetic waves of a specific frequency. This frequency selective surface is usually composed of metal sheets, metal wires or conductor materials, which are arranged on a substrate material to form a periodic structure. The working principle of FSS is based on the diffraction and reflection of incident electromagnetic waves by its periodic structure. By carefully designing the geometry, arrangement and size of FSS, electromagnetic waves within a specific frequency range can be controlled, such as selectively transmitting or reflecting signals of a specific frequency, while suppressing signals of other frequencies. FSS has outstanding applications in radar stealth technology. FSS can absorb or reflect radar signals within a certain frequency range, thereby reducing the radar cross-section and improving stealth performance. FSS is often formed by plasma etching on the surface of the substrate to form a fine structure or by coating, solution method or vacuum coating on the surface of the substrate, and the substrate includes metal or conductor.

[0003] FSS is usually a metal material and can be effectively combined with a metal substrate, but rarely combined with other materials. Due to the low surface energy of silicone rubber, it is difficult for metal materials to adhere to the surface of silicone rubber, the preparation process is limited, and it is difficult to process. Therefore, there is currently no FSS layer on the surface of an absorbing patch with silicone rubber as the substrate, and there is no processing method for preparing an FSS layer on the surface of such an absorbing patch.

[0004] In view of this, the present inventor provides a frequency selective surface structure, a double-layer absorbing patch and a preparation method to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and propose a frequency selective surface structure, a double-layer absorbing patch and a preparation method. By using liquid silicone rubber with the same matrix as the silicone rubber absorbing patch as the matrix of the printing paste, the FSS layer and the absorbing patch have a good bonding effect, which solves the problem that there is no FSS layer on the surface of the current silicone rubber absorbing patch and the problem that it is difficult to attach a metal FSS layer to the silicone rubber surface.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] On the one hand, the present invention provides a frequency selective surface structure, which includes N×M pattern units, a circular hole is etched at the center of each pattern unit, and four L-shaped strip apertures are etched at intervals on the outer circumference of the circular hole. The four L-shaped strip apertures are evenly distributed to form a square structure, each of the pattern units is a square, and square holes are etched at the four corners of each pattern unit, and any two square holes are symmetrical with the square structure as the center.

[0008] On the other hand, the present invention also provides a double-layer absorbing patch containing a frequency selective surface structure, including an FSS layer, an absorbing layer and a reflecting layer arranged on a backplane layer from top to bottom, and the structure of the FSS layer is the frequency selective surface structure as described in claim 1.

[0009] Furthermore, the thickness of the FSS layer is 0.01 mm to 0.03 mm, the absorbing layer is based on rubber and has a thickness of 0.5 mm to 1.2 mm, and the reflecting layer is based on rubber and has a thickness of 0.3 mm to 0.5 mm.

[0010] Furthermore, the double-layer absorbing patch containing the frequency selective surface structure has a real part of the complex dielectric constant of 11-12, an imaginary part of the complex dielectric constant of 0.5-1, a real part of the complex magnetic permeability of 1.1-1.7, and an imaginary part of the complex magnetic permeability of 0.2-0.5.

[0011] In another aspect, the present invention further provides a method for preparing a double-layer absorbing patch having a frequency selective surface structure, comprising the following steps:

[0012] Step 1, preparing the wave absorbing layer: gradually adding a set amount of absorbent, vulcanizing agent and coupling agent into the first silicone rubber for mixing to obtain a first rubber mix, placing the first rubber mix into a calender to form a sheet structure, and cutting the sheet structure of the first rubber mix into a specified structure and size to obtain the wave absorbing layer;

[0013] Step 2, preparing a reflective layer: gradually adding a conductive filler, a vulcanizing agent and a coupling agent to the second silicone rubber for mixing to obtain a second mixed rubber, placing the second mixed rubber in a calender to form a sheet structure, and cutting the second mixed rubber with the sheet structure into a specified structure and size to obtain a reflective layer;

[0014] Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization to obtain a double-layer absorbing patch.

[0015] Step 4, prepare the FSS layer: place the pre-made printing plate on the absorbing layer of the double-layer absorbing patch obtained in step 3, then evenly apply the pre-prepared printing slurry on the surface of the printing plate, and then put it into an oven for curing to obtain a double-layer absorbing patch containing a FSS layer.

[0016] Furthermore, in step 1, the absorbent is selected from flaky sendust powder, the mass ratio of the first silicone rubber to the flaky sendust powder is (3-4):1; the mass ratio of the coupling agent to the flaky sendust powder is (1-2):100; and the mass percentage of the vulcanizer in the rubber mixture is 1%-5%.

[0017] Furthermore, the mass ratio of the second silicone rubber to the silver-plated aluminum powder is (2-3):1; the mass ratio of the coupling agent to the silver-plated aluminum powder is (1-2):100; the mass percentage of the vulcanizing agent in the rubber mixture is 1% to 5%;

[0018] The first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and both have a hardness of 30 to 50 degrees.

[0019] Furthermore, in step 3, the specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows:

[0020] The overlapped absorbing layer and reflecting layer are loaded into the mold of a flat vulcanizer for a first-stage vulcanization treatment, wherein the first-stage vulcanization temperature is 160°C to 180°C and the time is 5min to 15min. After the first-stage vulcanization treatment is completed, the absorbing layer and reflecting layer are put into an oven for a second-stage vulcanization treatment, wherein the second-stage vulcanization temperature is 180°C to 200°C and the time is 2h to 4h.

[0021] Furthermore, in step 4, the surface structure of the printing plate is complementary to the frequency selective surface structure; the components of the printing paste include aluminum powder, liquid silicone rubber, a diluent and a dispersant, and the mass percentage of each component is:

[0022] The solid content of aluminum powder is 80% to 90%, the mass of the diluent accounts for 30% to 50% of the total mass of the printing paste, and the mass of the dispersant accounts for 0.5% to 1% of the total mass of the printing paste.

[0023] Furthermore, the preparation process of the printing paste is as follows: firstly, the aluminum powder is subjected to alkali washing treatment, and then added to the liquid silicone rubber, and then a diluent and a dispersant are added to the liquid silicone rubber containing the aluminum powder, and finally, the printing paste is obtained after being evenly dispersed by a disperser;

[0024] The alkali washing treatment of the aluminum powder is to use alkali solution to wash the aluminum powder to neutrality, and then put it into an oven for drying; the speed of the disperser is 800rpm to 1200rpm; the alkali solution is 15g / L NaOH solution.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) A double-layer absorbing patch containing a frequency selective surface structure proposed in the present invention contains the frequency selective surface structure proposed in the present invention. When electromagnetic waves are incident, strong resonance is generated in the frequency selective surface layer in the X-band, so that the double-layer absorbing patch of the present invention has an effective absorption bandwidth in the entire X-band; in addition, the FSS layer produces a prominent resonance effect at a specific frequency, achieving higher polarization stability. The reasonable structure and size design in the FSS layer make the double-layer absorbing patch of the present invention have better angular stability and stable absorbing performance at 0 to 45°.

[0027] 2) The printing paste of the present invention uses liquid silicone rubber as a matrix, which is the same as the silicone rubber matrix of the absorbing layer, so that the FSS layer and the absorbing layer have a good bonding effect, solving the problem that it is difficult to attach a metal FSS layer to the silicone rubber surface. In addition, the present invention is simple to prepare and low in cost.

[0028] 3) The present invention uses the same silicone rubber as the substrate of the absorbing layer as the substrate of the reflective layer, so that the combination of the reflective layer and the absorbing layer is more closely. In addition, the reflective layer using the silicone rubber substrate has a lower density and better flexibility than traditional metal materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0031] Figure 1 A schematic diagram of the structure of the frequency selective surface structure of the present invention;

[0032] Figure 2 A schematic diagram of a pattern unit of a frequency selective surface structure of the present invention;

[0033] Figure 3 It is a cross-sectional view of a double-layer absorbing patch having a frequency selective surface structure according to the present invention;

[0034] Figure 4This is a diagram showing the angular stability simulation results of a double-layer absorbing patch having a frequency selective surface structure according to the present invention;

[0035] Figure 5 This is a simulation result diagram of the polarization angle stability of the double-layer absorbing patch with a frequency selective surface structure of the present invention;

[0036] Figure 6 This is a diagram showing the simulation results of the electric field distribution of the double-layer absorbing patch having a frequency selective surface structure at 11.225 GHz of the present invention;

[0037] Figure 7 The present invention is a flow chart of a method for preparing a double-layer absorbing patch having a frequency selective surface structure.

[0038] Among them: 1 is a pattern unit; 11 is a round hole; 12 is an L-shaped strip aperture; 13 is a square hole. DETAILED DESCRIPTION

[0039] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.

[0040] On the one hand, see Figure 1 and Figure 2 An embodiment of the present invention provides a frequency selective surface structure, which includes N×M pattern units 1, a circular hole 11 is etched at the center of each pattern unit 1, and four L-shaped strip apertures 12 are etched at intervals on the outer periphery of the circular hole 11. The four L-shaped strip apertures 12 are evenly distributed to form a square structure. Each pattern unit 1 is a square, and square holes 13 are etched at the four corners of each pattern unit 1. Any two square holes 13 are symmetrical with the square structure as the center.

[0041] On the other hand, see Figure 3 An embodiment of the present invention also provides a double-layer absorbing patch containing a frequency selective surface structure, including an FSS layer, an absorbing layer and a reflecting layer arranged on a backplane layer from top to bottom, and the structure of the FSS layer is the frequency selective surface structure described above.

[0042] Furthermore, the FSS layer has a thickness of 0.01 mm to 0.03 mm, the absorbing layer has a rubber base material and a thickness of 0.5 mm to 1.2 mm, and the reflecting layer has a rubber base material and a thickness of 0.3 mm to 0.5 mm.

[0043] In this embodiment, since the upper part of the double-layer absorbing patch contains a frequency selective surface structure, a strong resonance is generated in the X-band frequency selective surface layer when electromagnetic waves are incident, so that the double-layer absorbing patch containing a frequency selective surface structure in this embodiment has an effective absorption bandwidth in the entire X-band. In addition, the FSS layer can also produce a prominent resonance effect at a specific frequency, achieving a higher polarization stability; the reasonable structure and size design of the FSS layer enable the present invention to have better angular stability, preferably, having stable absorbing performance at 0 to 45 degrees.

[0044] Furthermore, the real part of the complex dielectric constant of the double-layer absorbing patch containing the frequency selective surface structure is 11-12, the imaginary part of the complex dielectric constant is 0.5-1, the real part of the complex magnetic permeability is 1.1-1.7, and the imaginary part of the complex magnetic permeability is 0.2-0.5.

[0045] like Figure 1 and 2 As shown, the frequency selective surface structure includes 10×10 pattern units 1, each pattern unit 1 is a square with the same structure, and its side length is C. Square holes 13 are etched on the four corners of each pattern unit 1, and the size of the square hole 13 is A. The size of the circular hole 11 is R. The spacing between adjacent L-shaped strip apertures 13 is D, and the width of the L-shaped strip aperture 13 is E. The four L-shaped strip apertures 12 are evenly distributed to form a square structure with a side length of F.

[0046] The design effect of the double-layer absorbing patch with a frequency selective surface structure of this embodiment is described through simulation experiments. The geometric parameters of the FSS structure are shown in Table 1.

[0047] Table 1 FSS structural geometric parameters

[0048] parameter A B C value 2.5mm 15.5mm 21.4mm parameter D E F value 0.8mm 0.5mm 6mm

[0049] The angular stability of a double-layer absorbing patch with a frequency selective surface structure is simulated. Figure 4 It can be seen that the double-layer absorbing patch with a frequency selective surface structure has a relatively stable absorbing performance within 45°.

[0050] The polarization angle stability of a double-layer absorbing patch with a frequency selective surface structure is simulated. Figure 5 As shown. It can be seen that the double-layer absorbing patch with a frequency selective surface structure has excellent polarization stability.

[0051] The electric field distribution of a double-layer absorbing patch with a frequency selective surface structure at 11.225 GHz was simulated. Figure 6As shown, it can be found that the double-layer absorbing patch containing the frequency selective surface structure has a strong resonance effect at this frequency. It is the combined effect of the resonance of the geometric structure, the electric field focusing effect, the change of boundary conditions and the electromagnetic coupling effect that makes the absorption peak of the reflection loss the strongest at this time.

[0052] like Figure 3 As shown, the double-layer absorbing patch with a frequency selective surface structure has the first layer being the FSS layer, the second layer being the absorbing layer, the third layer being the reflecting layer, and the fourth layer being the backplane layer. Specifically, the backplane layer is the application surface of the absorbing patch, that is, the surface that needs to be invisible, which is not limited here.

[0053] In another aspect, an embodiment of the present invention provides a method for preparing a double-layer absorbing patch having a frequency selective surface structure, comprising the following steps:

[0054] Step 1, preparing the wave absorbing layer: gradually adding a set amount of absorbent, vulcanizing agent and coupling agent into the first silicone rubber for mixing to obtain a first rubber mix, placing the first rubber mix into a calender to form a sheet structure, and cutting the sheet structure of the first rubber mix into a specified structure and size to obtain the wave absorbing layer;

[0055] Step 2, preparing a reflective layer: gradually adding a conductive filler, a vulcanizing agent and a coupling agent to the second silicone rubber for mixing to obtain a second mixed rubber, placing the second mixed rubber in a calender to form a sheet structure, and cutting the sheet-like second mixed rubber into a specified structure and size to obtain a reflective layer;

[0056] Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization to obtain a double-layer absorbing patch.

[0057] Step 4, prepare the FSS layer: place the pre-made printing plate on the absorbing layer of the double-layer absorbing patch obtained in step 3, then evenly apply the pre-prepared printing slurry on the surface of the printing plate, and then put it into an oven for curing to obtain a double-layer absorbing patch containing a FSS layer.

[0058] Furthermore, in step 1, the absorbent is selected from flaky sendust powder, and the mass ratio of the first silicone rubber to the flaky sendust powder is (3-4):1; the mass ratio of the coupling agent to the flaky sendust powder is (1-2):100; the mass percentage of the vulcanizing agent in the rubber mix is ​​1%-5%, and the vulcanizing agent plays a corresponding role in the vulcanization process, and the commonly used ones can be selected, such as diphenylarsine peroxide, p-diphenylarsine, etc.

[0059] Furthermore, in step 2, the conductive filler is silver-plated aluminum powder, and the mass ratio of the second silicone rubber to the silver-plated aluminum powder is (2-3):1; the mass ratio of the coupling agent to the silver-plated aluminum powder is (1-2):100; the mass percentage of the vulcanizer in the rubber mix is ​​1% to 5%, and the vulcanizer can be commonly used, such as diphenylarsine peroxide, p-diphenylmethylarsine, etc.; wherein the first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and their hardness is 30 to 50 degrees.

[0060] Furthermore, in step 3, the specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows:

[0061] The overlapped absorbing layer and reflecting layer are loaded into the mold of a flat vulcanizer for a first-stage vulcanization treatment, wherein the first-stage vulcanization temperature is 160°C to 180°C and the time is 5min to 15min. After the first-stage vulcanization treatment is completed, the absorbing layer and reflecting layer are put into an oven for a second-stage vulcanization treatment, wherein the second-stage vulcanization temperature is 180°C to 200°C and the time is 2h to 4h.

[0062] Further, in step 4, the surface structure of the printing plate is complementary to the frequency selective surface structure, so that after the two overlap, both the front and back sides form a complete structure; the components of the printing paste include aluminum powder, liquid silicone rubber, a diluent and a dispersant, and the mass percentage of each component is:

[0063] The solid content of aluminum powder is 80% to 90%, the mass of the diluent accounts for 30% to 50% of the total mass of the printing paste, and the mass of the dispersant accounts for 0.5% to 1% of the total mass of the printing paste.

[0064] The diluent is an organic solvent such as toluene, xylene, acetone, etc.; the dispersant can be an alcohol, ketone or ether solvent.

[0065] Furthermore, the preparation process of the printing paste is as follows: firstly, the aluminum powder is subjected to alkali washing treatment, and then added to the liquid silicone rubber, and then a diluent and a dispersant are added to the liquid silicone rubber containing the aluminum powder, and finally, the printing paste is obtained after being evenly dispersed by a disperser;

[0066] The alkali washing treatment of the aluminum powder is to use alkali solution to wash the aluminum powder to neutrality, and then put it into an oven for drying; the speed of the disperser is 800rpm to 1200rpm; the alkali solution is 15g / L NaOH solution.

[0067] Preparation Example 1

[0068] The components of the printing paste include aluminum powder, liquid silicone rubber, diluent and dispersant, and the mass percentage of each component is:

[0069] The solid content of aluminum powder is 80%, the mass of the diluent accounts for 30% of the total mass of the printing paste, and the mass of the dispersant accounts for 0.5% of the total mass of the printing paste.

[0070] The preparation process of the printing paste is as follows: first, the aluminum powder is subjected to alkali washing to remove surface impurities and oxide film; then the alkali-washed aluminum powder is added to the liquid silicone rubber, and then a diluent and a dispersant are added to the liquid silicone rubber containing the aluminum powder so that the aluminum powder is evenly dispersed in the liquid silicone rubber, and finally a dispersing machine is used to evenly disperse the aluminum powder to obtain the printing paste.

[0071] The alkali washing treatment of aluminum powder is to use alkali solution to wash the aluminum powder to neutrality, and then put it into an oven to dry at 80°C for 1 hour; the speed of the disperser is 1000rpm; the alkali solution is 15g / L NaOH solution.

[0072] Preparation Example 2

[0073] The components of the printing paste include aluminum powder, liquid silicone rubber, diluent and dispersant, and the mass percentage of each component is:

[0074] The solid content of aluminum powder is 85%, the mass of the diluent accounts for 40% of the total mass of the printing paste, and the mass of the dispersant accounts for 0.75% of the total mass of the printing paste.

[0075] The above components were prepared according to the process of Preparation Example 1, and the speed of the disperser was 800 rpm.

[0076] Preparation Example 3

[0077] The components of the printing paste include aluminum powder, liquid silicone rubber, diluent and dispersant, and the mass percentage of each component is:

[0078] The solid content of aluminum powder is 90%, the mass of the diluent accounts for 50% of the total mass of the printing paste, and the mass of the dispersant accounts for 1% of the total mass of the printing paste.

[0079] The above components were prepared according to the process of Preparation Example 1, and the speed of the disperser was 1200 rpm.

[0080] Example 1

[0081] This embodiment provides a method for preparing a double-layer absorbing patch having a frequency selective surface structure, comprising the following steps:

[0082] Step 1, preparing an absorbing layer: gradually adding a set amount of flaky sendust powder, diphenylarsine peroxide and coupling agent A151 to the first silicone rubber, and mixing them on a rubber mixer. During the mixing process, the first silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the flaky sendust powder and the first silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a first rubber mix, the first rubber mix is ​​put into a calender and pressed into a sheet structure, and the sheet structure of the first rubber mix is ​​cut into a size corresponding to the size of the flat vulcanizer mold to obtain the absorbing layer;

[0083] The mass ratio of the first silicone rubber to the flaky sendust powder is 3:1; the mass ratio of the coupling agent to the flaky sendust powder is 1:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​1%;

[0084] Step 2, preparing a reflective layer: gradually adding silver-plated aluminum powder, diphenol p-methylphenylarsine and a coupling agent to the second silicone rubber, and mixing them on a rubber mixer. During the mixing process, the second silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the silver-plated aluminum powder and the second silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a second mixed rubber, the second mixed rubber is put into a calender and pressed into a sheet structure, and the sheet structure of the second mixed rubber is cut into a size corresponding to the size of the flat vulcanizer mold to obtain a reflective layer;

[0085] The mass ratio of the second silicone rubber to the silver-plated aluminum powder is 2:1; the mass ratio of the coupling agent to the silver-plated aluminum powder is 1:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​1%; the first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and both have a hardness of 30 degrees;

[0086] Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization to obtain a double-layer absorbing patch.

[0087] The specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows:

[0088] The overlapped absorbing layer and reflecting layer are loaded into the mold of a flat vulcanizer for a first-stage vulcanization treatment at a temperature of 160°C for 15 minutes. After the first stage vulcanization treatment, the absorbing layer and reflecting layer are put into an oven for a second stage vulcanization treatment at a temperature of 180°C for 4 hours.

[0089] Step 4, preparing the FSS layer: placing the printed plate prepared in advance on the absorbing layer of the double-layer absorbing patch obtained in step 3, and then evenly brushing the printing paste prepared in Preparation Example 1 on the surface of the printed plate, so that the printing paste flows into the surface of the double-layer absorbing patch through the through groove and then forms a structural shape corresponding to the FSS layer on the surface, and the double-layer absorbing patch with the FSS layer structure on the surface is put into an oven and cured at 180°C for 1 hour to form an FSS layer on the surface of the absorbing patch, thereby obtaining a double-layer absorbing patch containing an FSS layer.

[0090] In this embodiment, the thickness of the prepared FSS layer is 0.01 mm, the thickness of the absorbing layer is 0.5 mm, and the thickness of the reflecting layer is 0.3 mm.

[0091] In this embodiment, the real part of the complex dielectric constant of the double-layer absorbing patch with a frequency selective surface structure is 11-12, the imaginary part of the complex dielectric constant is 0.5-1, the real part of the complex magnetic permeability is 1.1-1.7, and the imaginary part of the complex magnetic permeability is 0.2-0.5.

[0092] Example 2

[0093] This embodiment provides a method for preparing a double-layer absorbing patch having a frequency selective surface structure, comprising the following steps:

[0094] Step 1, preparing an absorbing layer: gradually adding a set amount of flaky sendust powder, diphenylarsine peroxide and coupling agent A151 to the first silicone rubber, and mixing them on a rubber mixer. During the mixing process, the first silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the flaky sendust powder and the first silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a first rubber mix, the first rubber mix is ​​put into a calender and pressed into a sheet structure, and the sheet structure of the first rubber mix is ​​cut into a size corresponding to the size of the flat vulcanizer mold to obtain the absorbing layer;

[0095] The mass ratio of the first silicone rubber to the flaky sendust powder is 3:1; the mass ratio of the coupling agent to the flaky sendust powder is 1.5:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​3%;

[0096] Step 2, preparing a reflective layer: gradually adding silver-plated aluminum powder, diphenol p-methylphenylarsine and coupling agent A151 to the second silicone rubber, and mixing them on a rubber mixer. During the mixing process, the second silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the silver-plated aluminum powder and the second silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a second rubber mix, the second rubber mix is ​​put into a calender and pressed into a sheet structure, and the sheet structure of the second rubber mix is ​​cut into a size corresponding to the size of the flat vulcanizer mold to obtain a reflective layer;

[0097] The mass ratio of the second silicone rubber to the silver-plated aluminum powder is 2.5:1; the mass ratio of the coupling agent to the silver-plated aluminum powder is 1.5:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​3%; the first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and both have a hardness of 40 degrees;

[0098] Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization to obtain a double-layer absorbing patch.

[0099] The specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows:

[0100] The overlapped absorbing layer and reflecting layer are placed in a mold of a flat vulcanizer for a first-stage vulcanization treatment at a temperature of 170°C for 10 minutes. After the first stage vulcanization treatment, the absorbing layer and reflecting layer are placed in an oven for a second stage vulcanization treatment at a temperature of 190°C for 3 hours.

[0101] Step 4, preparing the FSS layer: placing the printed plate prepared in advance on the absorbing layer of the double-layer absorbing patch obtained in step 3, and then evenly brushing the printing paste prepared in Preparation Example 2 on the surface of the printed plate, so that the printing paste flows into the surface of the double-layer absorbing patch through the through groove and then forms a structural shape corresponding to the FSS layer on the surface, and the double-layer absorbing patch with the FSS layer structure on the surface is put into an oven and cured at 180°C for 1 hour to form an FSS layer on the surface of the absorbing patch, thereby obtaining a double-layer absorbing patch containing an FSS layer.

[0102] In this embodiment, the thickness of the prepared FSS layer is 0.02 mm, the thickness of the absorbing layer is 0.8 mm, and the thickness of the reflecting layer is 0.4 mm.

[0103] In this embodiment, the real part of the complex dielectric constant of the double-layer absorbing patch with a frequency selective surface structure is 11-12, the imaginary part of the complex dielectric constant is 0.5-1, the real part of the complex magnetic permeability is 1.1-1.7, and the imaginary part of the complex magnetic permeability is 0.2-0.5.

[0104] Example 3

[0105] This embodiment provides a method for preparing a double-layer absorbing patch having a frequency selective surface structure, comprising the following steps:

[0106] Step 1, preparing an absorbing layer: gradually adding a set amount of flaky sendust powder, diphenylarsine peroxide and coupling agent A151 to the first silicone rubber, and mixing them on a rubber mixer. During the mixing process, the first silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the flaky sendust powder and the first silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a first rubber mix, the first rubber mix is ​​put into a calender and pressed into a sheet structure, and the sheet structure of the first rubber mix is ​​cut into a size corresponding to the size of the flat vulcanizer mold to obtain the absorbing layer;

[0107] The mass ratio of the first silicone rubber to the flaky sendust powder is 4:1; the mass ratio of the coupling agent to the flaky sendust powder is 2:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​5%;

[0108] Step 2, preparing a reflective layer: gradually adding silver-plated aluminum powder, diphenol p-methylphenylarsine and coupling agent A151 to the second silicone rubber, and mixing them on a rubber mixer. During the mixing process, the second silicone rubber is triangularly folded into a triangular package (continuously wrapped in a triangular folding manner to make the silver-plated aluminum powder and the second silicone rubber evenly mixed), the folding number is not less than 10 times, and the mixing time is not less than 30 minutes to obtain a second rubber mix, the second rubber mix is ​​put into a calender and pressed into a sheet structure, and the sheet structure of the second rubber mix is ​​cut into a size corresponding to the size of the flat vulcanizer mold to obtain a reflective layer;

[0109] The mass ratio of the second silicone rubber to the silver-plated aluminum powder is 3:1; the mass ratio of the coupling agent to the silver-plated aluminum powder is 2:100; the mass percentage of the vulcanizing agent in the rubber mix is ​​5%; the first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and both have a hardness of 50 degrees;

[0110] Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization to obtain a double-layer absorbing patch.

[0111] The specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows:

[0112] The overlapped absorbing layer and reflecting layer are loaded into the mold of a flat vulcanizer for a first-stage vulcanization treatment at a temperature of 180°C for 5 minutes. After the first stage vulcanization treatment, the absorbing layer and reflecting layer are put into an oven for a second stage vulcanization treatment at a temperature of 200°C for 2 hours.

[0113] Step 4, preparing the FSS layer: placing the printed plate prepared in advance on the absorbing layer of the double-layer absorbing patch obtained in step 3, and then evenly brushing the printing paste prepared in Preparation Example 3 on the surface of the printed plate, so that the printing paste flows into the surface of the double-layer absorbing patch through the through groove and then forms a structural shape corresponding to the FSS layer on the surface, and the double-layer absorbing patch with the FSS layer structure on the surface is put into an oven and cured at 180°C for 1 hour to form an FSS layer on the surface of the absorbing patch, thereby obtaining a double-layer absorbing patch containing an FSS layer.

[0114] In this embodiment, the thickness of the prepared FSS layer is 0.03 mm, the thickness of the absorbing layer is 1.2 mm, and the thickness of the reflecting layer is 0.5 mm.

[0115] In this embodiment, the real part of the complex dielectric constant of the double-layer absorbing patch with a frequency selective surface structure is 11-12, the imaginary part of the complex dielectric constant is 0.5-1, the real part of the complex magnetic permeability is 1.1-1.7, and the imaginary part of the complex magnetic permeability is 0.2-0.5.

[0116] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.

[0117] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A frequency selective surface structure, characterized in that: The frequency selective surface structure comprises N×M pattern units (1), each pattern unit (1) is etched with a circular hole (11) at the center, four L-shaped strip apertures (12) are etched at intervals on the periphery of the circular hole (11), the four L-shaped strip apertures (12) are evenly distributed to form a square structure, each pattern unit (1) is a square, and square holes (13) are etched at the four corners of each pattern unit (1), and any two square holes (13) are symmetrical with the square structure as the center.

2. A double-layer absorbing patch with a frequency selective surface structure, characterized in that: It comprises an FSS layer, an absorbing layer and a reflecting layer which are arranged on the backplane layer in sequence from top to bottom, and the structure of the FSS layer is the frequency selective surface structure as claimed in claim 1.

3. The double-layer absorbing patch with a frequency selective surface structure according to claim 2, characterized in that: The thickness of the FSS layer is 0.01 mm to 0.03 mm, the wave absorbing layer is based on rubber and has a thickness of 0.5 mm to 1.2 mm, and the reflective layer is based on rubber and has a thickness of 0.3 mm to 0.5 mm.

4. The double-layer absorbing patch with a frequency selective surface structure according to claim 2, characterized in that: The double-layer absorbing patch with a frequency selective surface structure has a real part of a complex dielectric constant of 11-12, an imaginary part of a complex dielectric constant of 0.5-1, a real part of a complex magnetic permeability of 1.1-1.7, and an imaginary part of a complex magnetic permeability of 0.2-0.

5.

5. A method for preparing a double-layer absorbing patch having a frequency selective surface structure according to any one of claims 2 to 4, characterized in that: The following steps are involved: Step 1, preparing the wave absorbing layer: gradually adding a set amount of absorbent, vulcanizing agent and coupling agent into the first silicone rubber for mixing to obtain a first rubber mix, placing the first rubber mix into a calender to form a sheet structure, and cutting the sheet structure of the first rubber mix into a specified structure and size to obtain the wave absorbing layer; Step 2, preparing a reflective layer: gradually adding a conductive filler, a vulcanizing agent and a coupling agent to the second silicone rubber for mixing to obtain a second mixed rubber, placing the second mixed rubber in a calender to form a sheet structure, and cutting the second mixed rubber with the sheet structure into a specified structure and size to obtain a reflective layer; Step 3, preparing a double-layer absorbing patch: placing the absorbing layer on the reflecting layer, and placing the overlapping absorbing layer and the reflecting layer on a flat vulcanizing machine for vulcanization treatment to obtain a double-layer absorbing patch; Step 4, prepare the FSS layer: place the pre-made printing plate on the absorbing layer of the double-layer absorbing patch obtained in step 3, then evenly apply the pre-prepared printing slurry on the surface of the printing plate, and then put it into an oven for curing to obtain a double-layer absorbing patch containing a FSS layer.

6. The method for preparing a double-layer absorbing patch according to claim 5, characterized in that: In step 1, the absorbent is selected from flaky sendust powder, the mass ratio of the first silicone rubber to the flaky sendust powder is (3-4):1; the mass ratio of the coupling agent to the flaky sendust powder is (1-2):100; the mass percentage of the vulcanizer in the rubber mix is ​​1%-5%.

7. The method for preparing a double-layer absorbing patch according to claim 5, characterized in that: In step 2, the conductive filler is silver-plated aluminum powder, the mass ratio of the second silicone rubber to the silver-plated aluminum powder is (2-3):1; the mass ratio of the coupling agent to the silver-plated aluminum powder is (1-2):100; the mass percentage of the vulcanizing agent in the rubber mixture is 1% to 5%; The first silicone rubber in step 1 and the second silicone rubber in step 2 are of the same type, and both have a hardness of 30 to 50 degrees.

8. The method for preparing a double-layer absorbing patch according to claim 5, characterized in that: In step 3, the specific process of vulcanizing the overlapped absorbing layer and the reflecting layer is as follows: The overlapped absorbing layer and reflecting layer are loaded into the mold of a flat vulcanizer for a first-stage vulcanization treatment, wherein the first-stage vulcanization temperature is 160°C to 180°C and the time is 5min to 15min. After the first-stage vulcanization treatment is completed, the absorbing layer and reflecting layer are put into an oven for a second-stage vulcanization treatment, wherein the second-stage vulcanization temperature is 180°C to 200°C and the time is 2h to 4h.

9. The method for preparing a double-layer absorbing patch according to claim 5, characterized in that: In step 4, the surface structure of the printing plate is complementary to the frequency selective surface structure; the components of the printing paste include aluminum powder, liquid silicone rubber, a diluent and a dispersant, and the mass percentage of each component is: The solid content of aluminum powder is 80% to 90%, the mass of the diluent accounts for 30% to 50% of the total mass of the printing paste, and the mass of the dispersant accounts for 0.5% to 1% of the total mass of the printing paste.

10. The method for preparing a double-layer absorbing patch according to claim 9, characterized in that: The preparation process of the printing paste is as follows: firstly, the aluminum powder is subjected to alkali washing treatment, and then added to the liquid silicone rubber, and then a diluent and a dispersant are added to the liquid silicone rubber containing the aluminum powder, and finally a dispersing machine is used to disperse the aluminum powder uniformly to obtain the printing paste; The alkali washing treatment of the aluminum powder is to use alkali solution to wash the aluminum powder to neutrality, and then put it into an oven for drying; the speed of the disperser is 800rpm to 1200rpm; the alkali solution is 15g / L NaOH solution.